Twist Periodic Solutions in the Relativistic Driven Harmonic Oscillator - Daniel Núñez; Andrés Rivera (Abstract and Applied Analysis)
We study the one-dimensional forced harmonic oscillator with relativistic effects. Under some conditions of the parameters, the existence of a unique stable periodic solution is proved which is of twist type. The results depend on a Twist Theorem for nonlinear Hill’s equations which is established and proved here.